Patterns of Fitbit Use and Activity Levels Among African American Breast Cancer Survivors During an eHealth Weight Loss Randomized Controlled Trial. Issue 1 (January 2022) - Ferrante, Jeanne M.; Lulla, Aaron; Williamson, Julie D.; Devine, Katie A.; Ohman-Strickland, Pamela; Bandera, Elisa V.
Purpose: This study examined adherence with a physical activity tracker and patterns of activity among different subgroups of African American/Black breast cancer survivors (AABCS). Design: Secondary analysis of weight loss trial that used an activity tracker (FitBit) with or without a commercial eHealth program (SparkPeople) over 12 months. Setting and Subjects: AABCS (N = 44) in New Jersey. Measures and Analysis: Adherence with tracker use, steps per day, and active minutes per week were compared by demographic and clinical characteristics using nonparametric statistics. Results: Median adherence was over 6 days per week throughout the 12-months. Adherence was significantly correlated with steps and active minutes (p < 0.015). Groups with lower adherence included: those with 5 or more conditions (p = 0.039), had higher number of household members (p = 0.008), and younger than 60 years (p = 0.044). Median number of steps per day remained consistently around 7000 throughout 12 months. Factors associated with lower activity included: age> 60; retirement; higher number of household members, comorbidity, or baseline BMI; and those in the SparkPeople + Fitbit group. Self-monitoring, goal setting, and self-efficacy were significantly correlated with activity levels (p < 0.05). Conclusion: Use of a physical activity tracker may help increase activity levels in AABCS. Certain subgroups, e.g. those older than age 60 years, retired, with BMI over 40, higher number of comorbidities or more household members, may require additional interventions.